The Effects of the “Chabuca Granda in school” program on strengthening cultural identity in secondary education adolescents. - Arévalo Cárdenas, Charles Anyhony (2023)
The objective of the research was to evaluate the effectiveness of the educational program "Chabuca Granda en la Escuela" in the development of cultural identity in school adolescents from the San Martín de Porras district of Lima, Peru. A quantitative approach of quasi-experimental design was used, the sample was non-random of 52 students, belonging to the VI cycle of regular basic education at the secondary level. The sample was divided into a control and experimental group of 26 students. The Cultural Identity Scale pre-test was applied to both groups. The “Chabuca Granda in school program” was applied to the experimental group, which consisted of 12 sessions related to the work of the singer-songwriter while the control group did not undergo said program. At the end of the intervention, the same instrument was applied to both groups. The results showed a significant increase in the strengthening of the cultural identity of the students of the experimental group in the dimensions: customs, traditions, interculturality, way of life and appreciation of the work of Chabuca Granda. It is recommended to apply the educational program at other educational levels for the consolidation of cultural identity.